Analisis Penerapan Prinsip Etika Bisnis Islam dalam Pengelolaan UMKM "Bebek Cobek" Bangkalan Madura - Syafaah, Irbatus; Rohman, Abdur (Al-Ujrah | Jurnal Ekonomi Syariah, 2024)
This research aims to analyze the application of Islamic business ethics principles in the management of "Bebek Cobek" UMKM in Bangkalan Madura. The principles of Islamic business ethics that are applied include Unity/Tawhid, Balance, Freedom, Responsibility and Virtue. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with owners and employees as well as direct observation in the field. The research results show that the "Bebek Cobek" stall has implemented the principles of Islamic business ethics in its operations